The influence of the Dark Triad on various aspects of life - a review - Michał Andrzej Kozicz; Paulina Cuper; Ilona Jastrzębska; Krzysztof Bilecki; Hubert Gugulski; Michał Bado; Patrycja Nowoświat; Michalina Cuper (Nicolaus Copernicus University in Toruń, 2024)
Introduction: The Dark Triad is a construct devised by Paulhus and Williams in 2002. It comprises of three personality disorders: Narcissism, Machiavellianism and psychopathy, that are believed to be debilitating both to people exhibiting these traits and their social environment. Aim of the Study: The aim of the study was to collect and analyse current literature regarding the Dark Triad and the influence of its components on different areas of functioning.  Methods and Materials: Extensive research was conducted using PubMed and Google Scholar, with the primary focus on literature from the past 5 years. These databases were searched using "the Dark Triad" and its components names as entries to gather articles. Additionally, references from selected articles were included in the analysis. Results: Our article showed that the components of the Dark Triad influence many areas of functioning, although this influence is not always negative. Having all the traits of the Dark Triad is more likely to induce immoral behaviour than having the individual traits in isolation. Thus, further research of the Dark Triad is needed, especially regarding different facets of its components. Devising more in-depth questionnaires that would cover all sub-divisions of the Dark Triad components would largely bolster the research in this field.